Quality communication can improve patient-centred health outcomes among older patients: a rapid review - Sharkiya, Samer H. (BMC health services research, 2023)
Background Effective communication is a cornerstone of quality healthcare. Communication helps providers bond with patients, forming therapeutic relationships that benefit patient-centred outcomes. The information exchanged between the provider and patient can help in medical decision-making, such as better self-management. This rapid review investigated the effects of quality and effective communication on patient-centred outcomes among older patients. Methods Google Scholar, PubMed, Scopus, CINAHL, and PsycINFO were searched using keywords like “effective communication,“ “elderly,“ and “well-being.“ Studies published between 2000 and 2023 describing or investigating communication strategies between older patients (65 years and above) and providers in various healthcare settings were considered for selection. The quality of selected studies was assessed using the GRADE Tool. Results The search strategy yielded seven studies. Five studies were qualitative (two phenomenological study, one ethnography, and two grounded theory studies), one was a cross-sectional observational study, and one was an experimental study. The studies investigated the effects of verbal and nonverbal communication strategies between patients and providers on various patient-centred outcomes, such as patient satisfaction, quality of care, quality of life, and physical and mental health. All the studies reported that various verbal and non-verbal communication strategies positively impacted all patient-centred outcomes. Conclusion Although the selected studies supported the positive impact of effective communication with older adults on patient-centred outcomes, they had various methodological setbacks that need to be bridged in the future. Future studies should utilize experimental approaches, generalizable samples, and specific effect size estimates.